2019
DOI: 10.1099/ijsem.0.004690
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia acidiphila sp. nov., Paraburkholderia acidisoli sp. nov. and Burkholderia guangdongensis sp. nov., isolated from forest soil, and reclassification of Burkholderia ultramafica as Paraburkholderia ultramafica comb. nov.

Abstract: Three Gram-stain-negative, aerobic, motile and rod-shaped bacterial strains, 7Q-K02T, DHF22T and DHOM02T, were isolated from forest soil sampled at Dinghushan Biosphere Reserve, Guangdong Province, China. Strains 7Q-K02T, DHF22T and DHOM02T grew at 4–37, 4–42 and 12–37 °C, pH 3.0–8.5, 3.5–8.5 and 5.0–8.0, and in the presence of 0–3.0, 0–3.5 and 0–2.5 % (w/v) NaCl; with optima at 28–33, 28 and 28–33 °C, pH 3.5–6.5, 4.0–5.5 and 6.5–7.0, and 0–1.5, 0–1.5 and 0.5–1.5 % (w/v) NaCl, respectively. Strains 7Q-K02T and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Both B. novacaledonica and B. ultramafica were co-characterized and classified within Burkholderia ( Guentas et al, 2016 ), however, based on phylogenomics, these species belong to the genera Caballeronia and Paraburkholderia , respectively ( Supplementary Table 4 ). Recently, both species have been re-classified as Caballeronia novacaledonica ( Lozano et al, 2021 ) and Paraburkholderia ultramafica ( Gao et al, 2021 ), respectively. While B. dabaoshanensis is already recognized as a member of the genus Trinickia in the literature ( Estrada-de los Santos et al, 2019 ), NCBI taxonomy still recognized the species as Burkholderia during this study.…”
Section: Resultsmentioning
confidence: 99%
“…Both B. novacaledonica and B. ultramafica were co-characterized and classified within Burkholderia ( Guentas et al, 2016 ), however, based on phylogenomics, these species belong to the genera Caballeronia and Paraburkholderia , respectively ( Supplementary Table 4 ). Recently, both species have been re-classified as Caballeronia novacaledonica ( Lozano et al, 2021 ) and Paraburkholderia ultramafica ( Gao et al, 2021 ), respectively. While B. dabaoshanensis is already recognized as a member of the genus Trinickia in the literature ( Estrada-de los Santos et al, 2019 ), NCBI taxonomy still recognized the species as Burkholderia during this study.…”
Section: Resultsmentioning
confidence: 99%
“…Horsman et al [32], based on their sequencing of the type strain of ‘ Pseudomonas acidophila ’ (ATCC 31363), have suggested that this species should be reclassified as ‘ Paraburkholderia acidophila ’. However, as there is already a validly named species Paraburkholderia acidiphila [88], we have chosen to name this species as Paraburkholderia acidicola . Isolated from soil in Japan.…”
Section: Description Of Paraburkholderia Acidicola Sp Novmentioning
confidence: 99%
“…In fact, and based on its phylogenomic analysis, B. ultramafica was formally proposed to be transferred to the Paraburkholderia genus [11]. The taxonomic rank of B.…”
Section: Full-textmentioning
confidence: 99%